Selfless, monarchists, intellectuals, trade unionists and betrayers. Domestic workers, their representations and mobilizations - Dios Fernández, Eider de (Hispania Nova, 2020)
During the years between 1920 and 1938, different models of women coexisted and, at the same time, the images of the maids were diversified. During the dictatorship of Primo de Rivera, domestic service was not considered a job. During the Second Republic, although officially the domestic service was considered as a job, no modifications were made to make this incorporation practice. Anyway, during these years for the first time these women could unionize and denounce their bosses, organize mobilizations which would change the image of the maids for a long time.